Phase diagrams for alkali-activated slag binders. (May 2017) - Myers, Rupert J.; Bernal, Susan A.; Provis, John L.
Abstract: Phase diagrams for alkali-activated slag (AAS) binders are simulated at (metastable) thermodynamic equilibrium, spanning the relevant compositional envelopes for these materials. The phase diagrams are generally consistent with experimental observations in the literature, dominated by calcium (alkali) aluminosilicate hydrate (C-(N-)A-S-H) gels and Mg-Al layered double hydroxides. Relationships between the stabilities of the predicted solid phase assemblages, pore solution compositions, and the bulk chemical composition are identified, yielding an improved understanding of AAS binder chemistry. Strätlingite is predicted at low to intermediate Si concentrations and at high Al content, while zeolites (and thus most likely also disordered alkali-aluminosilicate (hydrate) gels) tend to precipitate at higher concentrations of both Si and Al; katoite and AFm-type phases are stabilised at intermediate levels of CaO + Al2 O3  + MgO. The application of these results in designing AAS binders can enable the phase assemblages and chemical properties of these materials to be more precisely controlled.